PENGGUNAAN METODE SAMBUNG SAMPING PADA BEBERAPA KLON KAKAO (Theobroma cacao L.) SEBAGAI SUMBER BAHAN TANAM - Josina Irene Brigetha Hutubessy (AGRICA, 2020)
Side grafting technology, side grafting is a cocoa plant improvement technique that is done by inserting the stem of superior clones. This study aims to determine the effect of Janis entries on the side grafting growth of cocoa plants and the types of good entries in the growth of side grafting cacao plant.The plan used in this study was a randomized block design (RBD) with treatments used were local clone actress (E1), superior clone actress ICCRI 03 (E2), superior clone actress ICCRI 04 (E3), Sulawesi superior clone 01 (E4) ), Superior actress of Sulawesi Clone 02 (E5). The observational variables in this study were the percentage of survival, total plant leaves, plant area. The results of the study aimed that the treatment of superior clone entries had an effect on the observed variables of survival rates, total number of leaves of plants, leaf area. The type of entris that gives the best effect on the side grafting growth of cacao plant seeds is the superior Sulawesi clone actress 02.